HEALTHY HEART EXERCISE ON BLOOD PRESSURE REDUCTION IN ELDERLY PRODUCTIVE - Mariati, Lusia Henny; Putri Hadia, Matilda; Jehani, Yohana (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Hypertension is a significant cause of premature death worldwide. One of the management of hypertension in the elderly is healthy heart exercise. This activity aims to determine the effect of healthy heart exercise in reducing blood pressure in productive elderly in the Bangka Kenda Health Center area. The population in this activity is productive elderly (45-59 years) with hypertension first degree. Activities consist of counseling on hypertension and healthy heart exercise. The exercise program was carried out for three weeks and done twice a week. After the first week of exercise, there was no significant change in blood pressure in the elderly with first-degree hypertension. After exercising in the second week, blood pressure slowly decreased. Exercise in the third week, blood pressure experienced a significant change. The analysis of changes in blood pressure in the elderly showed a significant effect of healthy heart exercise series one on changes in systolic and diastolic blood pressure in productive elderly (p-value 0.000 <0.05). The average blood pressure value decreased from the first-degree hypertension category to a normal high. There is a change in knowledge about hypertension before and after being given counseling. Healthy heart exercises one series is an alternative non-pharmacological treatment to reduce blood pressure in productive elderly.